Pengaruh Pola Asuh Orang Tua Single Parent Terhadap Kepribadian dan Religiusitas Anak di MTsN 2 Kaur Provinsi Bengkulu - Dena Puja Puspita (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The purpose of this study is (1) To determine the extent of the influence of single parent parenting patterns on children's personality at Madrasah Tsanawiyah (Mts) N 2 Kaur, Bengkulu Province. (2) To determine the extent of the influence of single parent parenting patterns on children's religiosity at Madrasah Tsanawiyah (Mts) N 2 Kaur, Bengkulu Province. This type of research is quantitative research with an associative approach, the research instruments are questionnaires, documentation and observation, data analysis techniques used are basic assumption tests, classical assumption tests, and hypothesis tests using simple linear regression. Research results (1) There is an influence of single parent parenting patterns on personality at MTs Negeri 2 Kaur which is shown in the calculated t (2.753) > t table (5% = 1.70) and a significance level of 0.513 < 0.05. So that in this test it shows that Ha is accepted. This means that there is an influence of single parent parenting patterns on personality at MTs Negeri 2 Kaur, with the results of determining the influence of single parent parenting patterns on personality at MTs Negeri 2 Kaur of 37.6%. (2) There is an influence of single parent parenting patterns on student religiosity at MTs Negeri 2 Kaur which is shown in the t count (2.812) > t table (5% = 1.70) and a significance level of 0.007 < 0.05. So in this test it shows that Ha is accepted. This means that there is an influence of single parent parenting patterns on student religiosity at MTs Negeri 2 Kaur. with the results of determining the influence of single parent parenting patterns on student religiosity at MTs Negeri 2 Kaur of 42.1%.